Palinomorfos de afinidad incierta en la perforación DI.NA.MI.GE. 254 “Paso De Las Toscas” (Pérmico Inferior), Cuenca Paraná, Uruguay - Gutierrez, Pedro Raul (2015)
An assemblage of palynomorphs (acritarchs, algae, fungi among other constituent elements of uncertain affinity) both autochtonous and reworked from San Gregorio Formation and Melo (well DI.NA.MI.GE. No. 254 “Paso de Las Toscas”), Paraná Basin, Uruguay, was analysed in this study. The cisuaralians microfloras are mostly indicative of fresh to mixohaline water environments. Notwithstanding, palynomorphs indicative of marine conditions (mainly Micrhystridium) are registered at 349 and 306 mbbp (San Gregorio Formation), and 282, 241, 168 and 139 mbbp (Frayle Muerto Member). The reworked specimens are restricted to some samples of San Gregorio Formation and a sample in the base of Frayle Muerto Member. The results are in accordance to the depositional setting of the sedimentary units as well as with the sea level changes during the time interval considered